PELAKSANAAN UPACARA RITUAL DALAM TANTRAYANA - Rita Istari (BRIN, 2002)
One of the characteristics of culture in Indonesia is the emergence of a process of assimilation or synthesis between local traditional elements and the culture that came from India. Likewise, the Tantrayana sect in Indonesia has had a lot of influence from local culture or local culture. The continuity of the Tantrayana school until now can be found in the arts and customs. For example: in Balinese art, there are stories of Calon Arang, Rangdha and Sarong related to witchcraft, as well as in intoxicating dances (Javanese: Tayuban). Meanwhile, in customs, you can find sacrificial ceremonies such as tabuh rah, metajen and mecaru. Apart from that, the ceremonies of worshiping ancestral spirits and invoking fertility by using opium as offerings can also be considered as remnants of elements of the Tantrayana tradition.